2017
DOI: 10.1002/2016jc012353
|View full text |Cite
|
Sign up to set email alerts
|

Observed cold filaments associated with mesoscale eddies in the South China Sea

Abstract: Unusual cold filaments are uncovered during the spring intermonsoon season in the South China Sea (SCS) using a suite of satellite observations. They have a width of about 100 km on average and extend several hundreds of kilometers offshore on the sea surface, providing significant cross‐shelf transport of heat and nutrients. The eastward current associated with mesoscale eddies in spring in the western SCS found to play an important role in the filament formation by advecting coastal cold waters far offshore.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…As a result, signatures of coastal and offshore upwellings frequently co-occur, challenging the determination of the reference SST, in which influences of upwelling and land effect caused by bounding of islands are NGO AND HSIN 10.1029/2020JC016892 5 of 23 considered insignificant. Second, SSTs over the SCS basin suffers strong interannual climate variability (Chao et al, 1996b;Dippner et al, 2007;Fang et al, 2012;Kuo et al, 2004;Li et al, 2017;Park & Choi, 2017;Shu et al, 2016;Wang et al, 2002;Xie et al, 2003;Zhao & Tang, 2007), that is, background SST in the SCS basin may be greatly leveled up/down by climate variability. Thus, using a fixed (or constant) reference SST value, such as the climatological SST, could ignore the influence of the interannual change of intrinsic SST over the SCS basin, resulting in an underestimate/overestimate of SSTUI.…”
Section: Sst-based Upwelling Indexmentioning
confidence: 99%
“…As a result, signatures of coastal and offshore upwellings frequently co-occur, challenging the determination of the reference SST, in which influences of upwelling and land effect caused by bounding of islands are NGO AND HSIN 10.1029/2020JC016892 5 of 23 considered insignificant. Second, SSTs over the SCS basin suffers strong interannual climate variability (Chao et al, 1996b;Dippner et al, 2007;Fang et al, 2012;Kuo et al, 2004;Li et al, 2017;Park & Choi, 2017;Shu et al, 2016;Wang et al, 2002;Xie et al, 2003;Zhao & Tang, 2007), that is, background SST in the SCS basin may be greatly leveled up/down by climate variability. Thus, using a fixed (or constant) reference SST value, such as the climatological SST, could ignore the influence of the interannual change of intrinsic SST over the SCS basin, resulting in an underestimate/overestimate of SSTUI.…”
Section: Sst-based Upwelling Indexmentioning
confidence: 99%
“…This eastward jet can then split and form an anticylonic eddy in the south and a cyclonic eddy in the north: Xu et al (), Fang et al (), and Xie et al (), Xie et al () indeed showed that the eastward jet is often centered between an eddy dipole caused by the orographic‐induced wind stress curl off southern Vietnam. The location of the eddy dipole, eastward jet, and associated coastal upwelling can vary over a wide range of latitude (Chen & Wang, ; Li et al, , ) from 10°N to 17°N with a mean position around 12°N (Li et al, ). A large, offshore area of cool SST ~28 °C (compared to ~29 °C in the surrounding area) is also observed north of the eastward jet, due to both advection of coastal upwelled water and offshore Ekman pumping associated with positive wind stress curl (Xie et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The lifespan of meroplanktonic hydromedusae varies between a few hours to a few years, but most species have a lifespan of more than 2 months (Brock and Strehler, 1963;Roosen-Runge, 1970;Mills, 1993). The velocity of the southwest wind jet was 30-110 cm•s −1 (Fang et al, 1997;Chen et al, 2012;Li et al, 2017;Da et al, 2019), and it will take a maximum of about 3 weeks for the coastal water transported to the farthest station (B3, 550 km off the coastline) in this study. The meroplanktonic hydromedusae can be carried to the WJR by horizontal transport considering the longevity of jellyfish and the age of water.…”
Section: Discussionmentioning
confidence: 77%
“…Additionally, the wind curl force of the southwest wind jet causes the double gyre circulation to form in the SCS with a northern cyclonic gyre and a southern anticyclonic gyre (Kuo et al, 2000;Metzger, 2003;Da et al, 2019;Ngo and Hsin, 2021). The cold coastal water is transported to the open SCS under the combined influence of the southwest wind jet and southern anticyclonic gyre, forming a clear cold filament in the sea surface temperature (Li et al, 2017;Huang et al, 2020;Sun and Lan, 2021). Generally, the cold coastal water could spread eastward over most of the central SCS (approximately 115 • E) in summer (Xie et al, 2003;Chen et al, 2021).…”
Section: Introductionmentioning
confidence: 99%